A non-randomized pre-post pilot study of cooling bed sheets in hot sleeping people - Weaver, Matthew D.; Qadri, Salim; Ejikeme, Chidera; Quan, Stuart F.; Czeisler, Charles A.; Robbins, Rebecca (Frontiers in Sleep, 2025)
IntroductionSleeping hot is a common barrier to good sleep. Characteristics of the sleep environment may impact temperature regulation and sleep. We tested the effectiveness of one brand of bed sheets that advertise cooling properties on sleep and vasomotor symptoms.MethodsParticipants were recruited through multiple channels that included potential customers of the intervention sheets and targeted online advertisements. Participants completed a baseline questionnaire, daily electronic diary for 6 weeks, and an end-of-study questionnaire. Assessments included the Pittsburgh Sleep Quality Index and Restorative Sleep Questionnaire. Daily diaries assessed sleep, mood, and perceived temperature during sleep. Within-person responses were compared before and after use of the intervention bed sheets.Results64 participants provided 2,627 total days of data. The study sample was 89% female, mean age 48 (SD 12). Sixty-nine percent of participants reported improved sleep quality after implementing the intervention. Mean improvement on the Pittsburgh Sleep Quality Index was 1.9 (95% CI 1.3–2.6), from 8.0 (SD 3.0) to 6.1 (SD 2.5) at end-of-study. The proportion of participants reporting trouble sleeping due to feeling too hot was reduced from 82.5 to 39.7%. Reported sleep duration increased 26 min (95% CI 14–38 min), from 6.5 h (SD 1.0) to 7.0 h (SD 0.8). Participants also reported improvements in night sweats, restorative sleep, mood, and alertness.ConclusionIndividuals reported improvements on several dimensions of sleep health, reductions in night sweats, and less sleep disruption due to sleeping too hot after implementing the intervention bed sheets. These findings warrant replication in a randomized, placebo-controlled design.